2021
DOI: 10.36416/1806-3756/e20200569
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-associated pneumonia in patients on prolonged mechanical ventilation: description, risk factors for mortality, and performance of the SOFA score

Abstract: Objetivo: A pneumonia associada à ventilação mecânica (PAVM) é uma séria complicação da ventilação mecânica (VM). Entretanto, dados sobre PAVM em pacientes em VM prolongada (VMP) são escassos. Nosso objetivo foi descrever as características de pacientes com PAVM em VMP e identificar fatores associados à mortalidade. Métodos: Estudo de coorte retrospectivo incluindo pacientes com PAVM em VMP. Foram registradas características basais, bem como as taxas de mortalidade em 30 e 90 dias. As variáveis associadas à mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
(93 reference statements)
2
10
1
1
Order By: Relevance
“…The extubation failure in patients in the VAP group was also higher than in the non-VAP group but not statistically significant. A recent study reported that the 30-day mortality rate after the diagnosis of VAP among adults was 30%, which is compatible with our study [ 12 ]. A meta-analysis of 6284 individual patient data from 24 VAP prevention trials has revealed a 30% overall mortality rate of 848 adult VAP patients, comparable to our study [ 6 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The extubation failure in patients in the VAP group was also higher than in the non-VAP group but not statistically significant. A recent study reported that the 30-day mortality rate after the diagnosis of VAP among adults was 30%, which is compatible with our study [ 12 ]. A meta-analysis of 6284 individual patient data from 24 VAP prevention trials has revealed a 30% overall mortality rate of 848 adult VAP patients, comparable to our study [ 6 ].…”
Section: Discussionsupporting
confidence: 93%
“…A systematic review by Arabi and colleagues on the incidence of VAP in developing countries demonstrated that the VAP rate was higher in developing countries compared to the National Healthcare Safety Network (NHSN) benchmark rates [ 12 - 14 ]. This higher rate may be attributed to various reasons, including lack of expertise, insufficient medical resources and modern technologies, inadequate nurse-to-patient staffing ratio, overloaded ICUs, and poor compliance with the guidelines [ 15 - 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meropenem was formerly used in our institution in certain patients with carbapenem-resistant Acinetobacter baumannii (CRAB) in combination with high-dose sulbactam. The predictor of 14-day mortality in CRAB was the severity of illness (OR = 1.38 for each 1-point increase in SOFA score; 95% CI: 1.21, 1.56) ( 36 ). Our study also found that SOFA score is one of the predictors of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States of America, the incidence ranges from 1 to 2.5 cases per 1000 days on IMV, while in Brazil and Europe, respective incidences of 16.8 and 18.3 episodes per 1000 days on IMV have been reported [ 3 , 4 ]. VAP has been associated with a greater number of antibiotic prescriptions in the ICU, longer IMV time, difficulty weaning from ventilation, longer hospital stay, and higher health-related costs [ 5 , 6 ]. Although VAP worsens the clinical condition of patients in the short term and increases the hospital mortality rate in the long term [ 6 , 7 ], little is known about its long-term consequences on lung and muscle function [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…VAP has been associated with a greater number of antibiotic prescriptions in the ICU, longer IMV time, difficulty weaning from ventilation, longer hospital stay, and higher health-related costs [ 5 , 6 ]. Although VAP worsens the clinical condition of patients in the short term and increases the hospital mortality rate in the long term [ 6 , 7 ], little is known about its long-term consequences on lung and muscle function [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%